Review paperRole of cyclooxygenase-2 in cervical cancer - Klimek, Małgorzata; Urbański, Krzysztof; Kojs, Zbigniew; Karolewski, Kazimierz; Pudełek, Jacek; Blecharz, Paweł (Archives of Medical Science, 2009)
Concurrent radiation and chemotherapy is a standard treatment of patients with cervical cancer in FIGO stages IB2-IVA. Chemotherapy given in the same time as irradiation improved survival significant, but not involves all patients. Cancer recurrence is the most common treatment failure in patients with advanced tumor. Further improvement in the treatment of advanced cases is essential. The increasing knowledge about new biologic markers and better ability to predict risk of cancer recurrence is very important for construction of more effective treatment strategies. Currently, there is considerable interest of role of cyclooxgenase-2 in cervical neoplasia. A lot of cancers in different localizations appear to overexpress the cyclooxygenase-2, which may have an important role in carcinogenesis. Ongoing clinical trials, clinical studies have shown the positive therapeutic effect of COX-2 inhibitors and may allow to increase understanding of this novel targeted approach for cervical cancer control.